The Presumption of Liberty and the Public Interest: Medical Marijuana and Fundamental Rights - Randy E. Barnett (Washington University Journal of Law & Policy, 2006)
As part of this lecture series on lawyering in the public interest, I decided to talk about my pro bono involvement in the medical cannabis case of Gonzales v. Raich, which I and three other lawyers brought on behalf of Angel Raich and Diane Monson. There are three topics I want to discuss: the first is how I got involved in doing this, which is a question I get asked all the time; the second is to describe the theory we took to the Supreme Court, which prevailed in the Ninth Circuit but was ultimately rejected by the Court on a vote of six to three; and finally, because the case still continues, I want to explain our current claims, which are based on the Due Process Clause of the Fifth Amendment and on the Ninth Amendment. In particular, I want to talk to you about how our current theory relates to what you have all learned or should be learning in your constitutional law classes. I think the problems we face in our case illustrate the weakness of the current approach to using the Due Process Clause to protect liberty—that I am compelled, as a litigator, to remain within—and why a “presumption of liberty,” which I have argued for in my scholarship, would be preferable to the current approach.
Keywords: Marijuana – Therapeutic use; Citizen suits (Civil procedure); Due process of law; Interstate commerce clause (Constitutional law); Medical marijuana; Presumptions (Law); United States